2019
DOI: 10.3201/eid2502.180299
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularisInfection, Southern Ontario, Canada

Abstract: Alveolar echinococcosis, the disease caused by infection with the intermediate stage of the Echinococcus multilocularis tapeworm, is typically fatal in humans and dogs when left untreated. Since 2012, alveolar echinococcosis has been diagnosed in 5 dogs, 3 lemurs, and 1 chipmunk in southern Ontario, Canada, a region previously considered free of these tapeworms. Because of human and animal health concerns, we estimated prevalence of infection in wild canids across southern Ontario. During 2015–2017, we collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 32 publications
(45 reference statements)
2
61
1
Order By: Relevance
“…After a small cluster of domestic dogs that had diagnoses of E. multilocularis infection in Ontario, a survey of wild canid carcasses was conducted across southern Ontario. Of 460 fecal samples, 23% were positive by PCR for E. multilocularis DNA (13). Of the 18 affected public health units, 10 had clustering with higher prevalence and were in regions with human population densities of up to 1,700 persons/km 2 .…”
Section: Discussionmentioning
confidence: 99%
“…After a small cluster of domestic dogs that had diagnoses of E. multilocularis infection in Ontario, a survey of wild canid carcasses was conducted across southern Ontario. Of 460 fecal samples, 23% were positive by PCR for E. multilocularis DNA (13). Of the 18 affected public health units, 10 had clustering with higher prevalence and were in regions with human population densities of up to 1,700 persons/km 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This area was not previously shown to be endemic for the pathogen, and suggests a possible change in geographic distribution. 2 Despite this, the annual incidence of human alveolar echinococcosis in endemic regions is believed to be low (0.03-1.2 cases per 100 000 inhabitants). 3 To our knowledge, 1 published case report of human alveolar echinococcosis acquired in Canada (Winnipeg, Manitoba) exists in the literature, which was published in 1937.…”
Section: Epidemiologymentioning
confidence: 99%
“…in pigs, and thus interrupting the life cycle. The disease is a growing threat to public health in the northern hemisphere ( Gottstein et al, 2015 , Kotwa et al, 2019 ) and has been shown to be highly endemic in Switzerland, with the incidence of human AE significantly increasing in recent years ( Gottstein et al, 2015 , Lachenmayer et al, 2019 ). In contrast to human cases, infections in animals – either as final or intermediate hosts - are reportable in Switzerland ( Anonymous, 1995 ).…”
Section: Introductionmentioning
confidence: 99%